Existence of independent learning curriculum and portrait of ideal curriculum management in laboratory schools - Maisyaroh, Maisyaroh; Wiyono, Bambang Budi; Chusniyah, Tutut; Adha, Maulana Amirul; Valdez, Anabelie Villa; Lesmana, Indra (Journal of Education and Learning (EduLearn), 2024)
Each schools have the autonomous right to manage and develop an independent curriculum according to its potential. However, the implementation of the independent learning curriculum is dependent on proper management at the school level, so there may be obstacles faced by schools in managing the independent learning curriculum. The purpose of this study is to investigate the concept and problems, as well as school strategies in managing an independent learning curriculum in laboratory schools. This research was studied qualitatively with a multi-site study design. Data collection was conducted through focus group discussions (FGDs) with semistructured interviews, observations, and documentation studies. Data validity was checked using source triangulation, discussion among fellow researchers, and adequacy of reference materials. Data analysis techniques used constant comparative analysis. The results show that learning activities in the independent curriculum emphasize character education and the achievement of students' happiness in learning, and schools implement differentiated learning and simplify the values contained in P5 through projects and fun learning. This research contributes theoretically and practically, by complementing previous literature and can be a guide for school managers in order to ideally manage an independent curriculum.